Canopy Leaching Rather than Desorption of PM2.5 From Leaves Is the Dominant Source of Throughfall Dissolved Organic Carbon in Forest - Ji‐Yeon Cha; Seung‐Cheol Lee; Eun‐Ju Lee; Kyuyeon Lee; Hojin Lee; Hyun Seok Kim; Jinho Ahn; Neung‐Hwan Oh (Geophysical Research Letters)
Abstract Dissolved organic carbon (DOC) in throughfall plays a vital role in providing carbon and energy to organisms in forests. We utilized carbon isotope analysis to allocate the sources of throughfall DOC, including leaching from plant tissues, PM2.5 deposition on plant foliage, and precipitation. Rainwater, PM2.5, and throughfall samples were collected from pine and oak forests between March and November 2021. The mean concentration of throughfall DOC was 7.9 mg L−1, approximately six times higher than that of rainfall. The mean Δ14C of throughfall DOC was −38.2‰, ∼200‰ higher than that of rainwater or PM2.5. Mass balance estimates revealed that canopy leaching contributed to ∼83% of throughfall DOC, while desorption of PM2.5 and rainwater accounted for only ∼3% and ∼14% of throughfall DOC, respectively. These results clearly highlight canopy leaching as the primary source of carbon input to the forest floor, with a relatively minor contribution from PM2.5 desorption on leaves.